Simbolisme Makna Dhahar Caos Besi dalam Serat Kagungan Dalem Angka 5: Symbolism Meaning Dhahar Chaos Iron in Fibers of the Inner Number 5 - Dewi, Dilla Anggraini Nur Auliana; Widihastuti, Rahma Ari (Information Technology and Science(ITScience), 2025)
The keris is an intangible cultural heritage that has deep philosophical, spiritual, and symbolic values ??in Javanese culture. The process of making it is not only technical but also ritualistic, reflecting the harmonious relationship between humans, nature, and spiritual forces. One important element in this process is dhahar caos or offerings offered to the metal as the primary material of the keris. This tradition is believed to be a form of symbolic communication that influences the character and quality of the resulting keris, employing a qualitative descriptive method with a Pierce semiotic approach, which involves three main concepts: icons, indexes, and symbols. This study utilizes primary data sources, including the Kagungan Dalem Number 5 manuscript, and supports these findings with secondary data from articles, books, and other relevant literature. The data collection technique is carried out through a heuristic reading technique. Data analysis employs a hermeneutic reading method that is conducted in depth to understand the meaning contained in the manuscript. The results of the study found 12 types of iron along with 20 offerings that have their own characters and powers as well as symbolic meanings, indicating that dhahar caos is not only part of a spiritual ritual, but also contains symbolic representations that describe the character of the metal and hopes for the strength and power of the keris. These symbols also serve as a form of nonverbal communication between humans and heirlooms. The results of this research are expected to expand the scope of Javanese cultural studies and contribute to the preservation of intangible heritage through the development of digital-based educational media.